Meaning in military service among reservists: Measuring the effect of prosocial motivation in a moderated-mediation model - Smaliukienė, Rasa; Bekesiene, Svajone; Kanapeckaitė, Rosita; Navickienė, Olga; Meidutė-Kavaliauskienė, Ieva; Vaičaitienė, Ramutė (Frontiers in Psychology, 2023)
Introduction The meaningful commitment to serve one’s country and the desire to defend others make military service unique compared to other human activities. This is especially true for the army reservists who are typically working in the civilian labor market and serving military for the short-term military training or military missions only. As scholars provide limited insights into the effects and influences of prosocial motivation on meaning in military service, this study contributes to the understanding of direct, mediated, and moderated processes which link prosocial motivation to meaning in military service among reservists. Specifically, the objective of this study was to examine both direct and indirect pathways interconnecting prosocial motivation and meaning in military service. The former is analyzed as a direct effect, while the latter includes the effects of role fit within the military environment, the soldiers’ self-efficacy, as well as the socio-moral climate of military organization—that is, a variable making military service an exceptional activity. Methods This study followed a quantitative method analysis by utilizing a hierarchical regression analysis which revealed direct, moderating, and mediating links between the variables. The analysis was based on a sample of 375 soldiers from the Active Reserve of the Lithuanian Armed Forces, and the data were collected before and after training exercises in one military unit (repeated measures). The effects on providing meaning to military service were evaluated using the following: Occupational Self-Efficacy Scale, Prosocial Motivation Scale, Motivation at Work Scale, and Socio-Moral Climate Scale. Prosocial motivation assumes meaning in military service among reservists through different, yet related, pathways. Results and discussion The direct pathway confirmed that reserve soldiers with higher levels of prosocial motivation experience a higher level of meaning in service. The indirect pathway indicated that role fit mediated this relationship. Following the latter, we found that prosocial motivation was a significant predictor of both role fit and meaning in military service. Finally, we confirmed the moderated-mediation effects of self-efficacy and socio-moral climate in our suggested models. The results can be used to improve training programs for reservists.